Thermal Energy Storage Integration Based on Pinch Analysis – Methodology and Application. Issue 5 (5th April 2017) - Olsen, Donald; Liem, Peter; Abdelouadoud, Yasmina; Wellig, Beat
Abstract: Reducing thermal energy use in industry is an effective way to improve energy efficiency. Process integration methods tackle this challenge, of which pinch analysis is a popular approach for identifying direct heat recovery measures. Many processes are batch processes that can profit from indirect heat recovery using thermal energy storage (TES). This paper presents a systematic conceptual TES integration methodology. In addition, functionality to support this methodology has been implemented in the PinCH software and is presented in a case study. Abstract : Thermal energy storage is important for improving heat integration in batch processes. To reduce energy consumption in such processes, practical tools for conceptual design are required. The PinCH software has been extended to include unique feature support based on the indirect source/sink profile to aid in the design of heat exchangers and storage networks based on pinch analysis.